Rab GTPases and the Autophagy Pathway: Bacterial Targets for a Suitable Biogenesis and Trafficking of Their Own Vacuoles - Lopez de Armentia, María Milagros (2016)
Autophagy is an intracellular process that comprises degradation of damaged organelles, protein aggregates and intracellular pathogens, having an important role in controlling the fate of invading microorganisms. Intracellular pathogens are internalized by professional and non-professional phagocytes, localizing in compartments called phagosomes. To degrade the internalized microorganism, the microbial phagosome matures by fusion events with early and late endosomal compartments and lysosomes, a process that is regulated by Rab GTPases. Interestingly, in order to survive and replicate in the phagosome, some pathogens employ different strategies to manipulate vesicular traffic, inhibiting phagolysosomal biogenesis (e.g., Staphylococcus aureus and Mycobacterium tuberculosis) or surviving in acidic compartments and forming replicative vacuoles (e.g., Coxiella burnetti and Legionella pneumophila). The bacteria described in this review often use secretion systems to control the host?s response and thus disseminate. To date, eight types of secretion systems (Type I to Type VIII) are known. Some of these systems are used by bacteria to translocate pathogenic proteins into the host cell and regulate replicative vacuole formation, apoptosis, cytokine responses, and autophagy. Herein, we have focused on how bacteria manipulate small Rab GTPases to control many of these processes. The growing knowledge in this field may facilitate the development of new treatments or contribute to the prevention of these types of bacterial infections.